Molecular and Spectroscopic Characterization of Green and Red Cyanine Fluorophores from the Alexa Fluor and AF Series. Issue 15 (5th August 2021) - Gebhardt, Christian; Lehmann, Martin; Reif, Maria M.; Zacharias, Martin; Gemmecker, Gerd; Cordes, Thorben
Abstract: The front cover artwork was provided by Gabriel Moya, a PhD student in the Cordes lab (LMU Biocenter Munich, Germany). The cover image shows an artistic impression of the chemical structures of two fluorophores investigated in the paper. Read the full text of the Article at 10.1002/cphc.202000935 . Abstract : "We have here studied the molecular and spectroscopic properties of Alexa Fluor 555 and Alexa Fluor 647 in relation to other cyanine fluorophores with known molecular structures…" This and more about the story behind the front cover can be found in the Article at 10.1002/cphc.202000935 .